Remember the definition of the tangent function:
![\tan \theta=(\sin \theta)/(\cos \theta)](https://img.qammunity.org/2023/formulas/mathematics/college/bg53xpwlozyrclgguit8zxk76l0i2mfiza.png)
Then, we notice that:
![\tan (\theta)=-\sqrt[]{(19)/(17)=}-\sqrt[]{((19)/(6))/((6)/(17))}=(\sin \theta)/(\cos \theta)](https://img.qammunity.org/2023/formulas/mathematics/college/fv94bqxia2ca9juldqbdbpnohg3b84l05b.png)
Then, we can conclude that:
![(\sin \theta)/(\cos \theta)=-\frac{\sqrt[]{(19)/(6)}}{\sqrt[]{(6)/(17)}}](https://img.qammunity.org/2023/formulas/mathematics/college/neybimcjycfikzt7p1eoeirhd0v9t674b8.png)
Something important to remember is that, in quadrant II, the value of sin(x) is positive, whereas the value of cos(x) is negative
So,
![\begin{gathered} \sin (\theta)=\sqrt[]{(19)/(6)} \\ \Rightarrow(1)/(\cos \theta)=-\frac{1}{\sqrt[]{(6)/(17)}} \\ \Rightarrow\cos \theta=-\sqrt[]{(17)/(6)} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/kt00t4so8go3lu9966svnjb6tnd6xth2eg.png)
Therefore, the answer to the question is option A